Oracle database 11g [ building Oracle XML DB applications - Wang, Jinyu , 1972- (McGraw Hill, 2011)
"Develop, debug, and administer data-backed XML applications using the expert instruction and best practices in this Oracle Press guide. Oracle Database 11g: Building Oracle XML DB Applications discusses the latest development tools, technologies, and components. Find out how to set up Oracle XML Database, build XML applications in Oracle JDeveloper 11g, work with XSLT stylesheets, and incorporate full-text search. Troubleshooting, performance tuning, and security are also covered in this comprehensive resource" -- Provided by publisher